The Formation of Effective Usage of Land Resources in Accounting, Analysis and Management of Agricultural Enterprises in the Market Conditions - TKAL, Yarmila S.; ABRAHAM, Yulia V.; TKACHENKO, Viktoriia V.; POLIATYKINA, Larysa I. (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The article is dedicated to the study of the need to intensify the state influences upon the efficiency of land resources usage. The technology of the rational land resources usage is advanced by way of reducing straw as organic fertilizer under direct contribution in the ground that provides spare facilities, raises the level to the efficiency of production, influences upon increasing of the fertility of the ground. Offences such as unauthorized seizure and misuse of land, removal of a fertile layer without permission, pollution of land, non-implementation of land reclamation cause significant damage to the state and owners of land, which leads to irreversible loss of land, quality and fertility. A methodical approach to assessing the improvement of information and analytical support for agricultural development is to create an effective system of formation, processing and transmission of analytical data of the accounting for the timely adoption of effective decisions at all levels of the agricultural sector. The result of this improved method of assessing include the issue of land conservation and rational use for the purpose of sustainable domestic land use. That is what caused the selection of research topics, defined goals, objectives and building its structure and trends.